Peran Audit Syariah dalam Memastikan Transparansi Penyaluran Dana Kebajikan (Zakat, Wakaf, Infaq) di Bank Syariah - Putri Humairah Napitupulu; Muhammad Syafril Nasution (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Islamic banks not only function as financial institutions but also act as managers of benevolent funds such as zakat, waqf, and infaq, which must be administered transparently, accountably, and in accordance with Islamic principles. This study aims to analyze the role of Sharia audit in ensuring the transparency of benevolent fund distribution in Islamic banks and to identify the challenges faced in its implementation. The research employs a qualitative approach through a literature review by examining various academic sources, regulations, and publications related to Sharia auditing, Sharia governance, and the management of benevolent funds. The findings indicate that Sharia audit plays a significant role in ensuring compliance with Islamic principles, improving the quality of reporting, strengthening accountability in fund management, and enhancing public trust in Islamic banks. Through monitoring and evaluation processes, Sharia audit helps minimize the risk of fund misuse and ensures that benevolent funds are distributed to eligible beneficiaries in line with their intended social and religious objectives. However, the implementation of Sharia audit still faces several challenges, including the absence of standardized reporting practices for benevolent funds, limited competencies of Sharia auditors, and insufficient disclosure regarding the sources and utilization of funds. Therefore, strengthening Sharia governance is necessary through the development of more comprehensive reporting standards, the enhancement of Sharia auditors’ competencies, and the expansion of audit coverage to include social aspects. These findings demonstrate that Sharia audit has a strategic role in improving transparency and accountability in the management of benevolent funds, thereby reinforcing public confidence in Islamic banks.